Analgesia acupuntural para la regulación menstrual en pacientes atendidas en el Policlínico Universitario "Josué País García". - Morales, Angel Alfonso Ximelis; Sánchez, Virgen Cruz; Fontanet, Jorge Joaquín Álvarez; Lage, Ada Legna Montoya; Freites, Gilberto Quevedo (MEDISAN, 2013)
A descriptive and cross-sectional study was carried out in 60 patients attended in the menstrual regulation department of "Josué País García" University Polyclinic of Santiago de Cuba, from April to June 2009, with the purpose of evaluating the results of acupuncture analgesia used to treat these females. Among the analyzed variables were age, education, occupation, severity of perceived pain, complications and satisfaction. To summarize the information the absolute and relative frequencies were used (percentage). The age group of 15-19 years, high school level, students, and bleeding as the most frequent complication and moderate pain as that of more severity predominated in the case material. Also, the effective treatment prevailed and there was an adequate satisfaction of the patients in the use of that technique.